(3eSfO YHO Hf MejO GdcTis - (3YHO Hf MejO Hf fUQ GdcSj, CHh eMeO,J (B249 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3MUjf Hf YeQ bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3ef ZT GdYQH de jONd ai TaGYJi hde Jfdg ehOJi s
(3BNQgG (B:s
(3Yf Ce Cjef CfgG SeYJ QShd Gddg Udi Gddg Ydjg hSde jhUi HYV Cgdg abGd dGJTQc HGddg TjFkG cGf GdehUi HgPg GdhUjI KhHGf QVi Gddg Yfg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HBNQ GdfSNI JMHjS GdhRjQ CHj GdMSf Ydi Hf jhSa GdhWGS SfI (B855s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B66s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs